Mitigating Risk in Construction Business: The Impact of Contractor Business Size and Risk Location (Office and Field) - Hanafi, Nufrizal Faried; Winarno, Setya (International Journal of Membrane Science and Technology, 2023)
This study aims to evaluate the relationship between the size of the construction business and the location of the risk with the risks that arise in construction projects in Indonesia. The method used is two-way anova analysis by sampling 90 construction projects in Indonesia. The independent variable in this study is the size of the construction business and the location of the risk, while the dependent variable is the risk on the construction project. The results showed that there is a significant relationship between the size of the construction business and the risks of construction projects in Indonesia. In addition, there is also a significant relationship between the location of risks and risks in construction projects in Indonesia. However, there was no significant interaction between the size of the construction business and the location of risk to risk in construction projects in Indonesia. This research contributes to the construction industry in Indonesia in evaluating the factors that affect risk in construction projects. By knowing the relationship between the size of the construction business and the location of the risk with the risk on the construction project, the contractor company can improve the risk management strategy to minimize the risk to the construction project in the future. Future research may consider other variables such as contractor experience and expertise as well as external factors such as market and political conditions to better understand the factors that influence risk in construction projects in Indonesia.